- #1

- 148

- 0

Sketch g(t) = f(-3t + 9).

I know how to work this out with trial and error:

t = 0 => g(t) = f(9) = 0

t = 1 => g(t) = f(6) = 0

t = 2 => g(t) = f(3) = 2

t = 3 => g(t) = f(0) = -3

t = 4 => g(t) = f(-3) = 0

etc...

How do I do this in a faster and more reliable way, taking into account all the coordinates?

I know how to work this out with trial and error:

t = 0 => g(t) = f(9) = 0

t = 1 => g(t) = f(6) = 0

t = 2 => g(t) = f(3) = 2

t = 3 => g(t) = f(0) = -3

t = 4 => g(t) = f(-3) = 0

etc...

How do I do this in a faster and more reliable way, taking into account all the coordinates?